(3GdceGd aj eYQaI CSeGA GdQLGds - (3YHO GdZfj Hf YHO GdhGMO Hf Ydj Hf SQhQ GdebOSj GdLeGYjdj GdOeTbj GdMfHdj, CHh eMeO, Jbj GdOjf,J (B600 (3g` s
(3ChdgG (B:s
(3ef JQLeI ef GSeg MGdjS hMGJe ef MQa GdMGA s
(3BNQgG (B:s
(3Edi HGH ef GSeg YHOGdedc s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B275s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B357 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B217 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1509s
Keywords: (3GdJGQjNs